Today Is My Day - Anushka Ravishankar (Tara publishiung, 2003)
People are always telling Tala what to do--from her father to her sister and her teachers . . . Tala plots sweet revenge, just for today. This wicked and witty story in verse celebrates the child's powers of imagination and fantasy. Lively art that captures the eccentricities of character and creative typeplay bring alive this irreverent and burlesque world that all children would love to identify with.
Keywords: Read Aloud Section - R -- Read Aloud Section - R